International cooperation of S. I. Subbotin Institute Geophysics, NAS of Ukraine for 2010—2020 - Starostenko, V. I.; Rusakov, O. M.; Yakimchik, A. I. (Geofizicheskiy Zhurnal, 2021)
The geological structure of the lithosphere of the main tectonic structures has been refined for the territory of Ukraine and adjacent regions of Slovakia, Poland, Romania, Russia, as well as Bulgaria, the Antarctic Peninsula (West Antarctica) and Southeast Asia, and new data have been obtained on geophysical impacts that can affect the environment. A geodynamic scenario has been developed for the formation of large-scale folding of the Fore- Dobrudzja Trough, the South Ukrainian monocline and the Ingul block of the Ukrainian Shield, caused by tectonic events associated with the closing of the Paleotethys and Neotethys oceans in the Mesozoic. In the Pripyat-Dnieper-Donets Basin, the structure of the earth’s crust and upper mantle can reflect different intensities of rifting, from its passive stage in the Dnieper Graben to active rifting in the Pripyat Trough. An analysis of the geoelectric structure of the Earth’s crust in the Ukrainian Eastern Carpathians indicates that seismic events occur mainly in resistive solid rock domainswhich surrounded by aseismic high conductive zones consisting of at least partially melted material. The present-day mutual position of the Ukrainian shield and Fennoscandia stabilized 1720—1660 Ma. The age, distribution, orientation and composition have been studied for the LatePalaeoproterozoicdykes in the Volyn, Ingul and Azov blocks of the Ukrainian Shield. Eastern Crimea and the Sorokin Trough are fragments of a tectonic wedge formed after the Paleocene. The geothermal conditions of the Intra-Carpathian region are due to subduction during the closure of the Pannonian sea basin and the collisional interaction of the Eurasian plate with the microplates system of this region. In Bulgaria, most earthquakes occur outside high-resistive domains. The tectonic stages are reconstructed for the formation of the northern part of the Antarctic Peninsula in the Mesozoic-Cenozoic. The relationship has been established between the geomagnetic field and climate change, with it being different for the Northern and Southern Hemispheres. The results have been obtained within the framework of 25 international projects and 6 temporary international target teams of S. I. Subbotin Institute of Geophysics, NAS of Ukraine consisting of researchers from 23 countries. The results are presented in 53 publications, 38 of which are indexed in the Web of Scienct database, and 32 papers are published in 20 international journals and special publications of 10 countries with different impact factors (from 0,101 to 4,214), whose average impact factor is 3,341, and the total one is 66,815.